2009
DOI: 10.1111/j.1744-7402.2009.02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3 Content on Crystallization Behavior, Microstructure, and Mechanical Properties of SiO2-Al2O3-CaO-MgO Glass-Ceramics

Abstract: The crystallization of glasses with general composition (61.87−x) %SiO2, x%Al2O3, 22.01% CaO, 6.24% MgO, 2.54% Na2O, 2.72% K2O, 0.58% TiO2, 3.34% Fe2O3, and 0.7% Cr2O3 (wt%) where x varies between 0% and 22% was investigated using differential thermal analysis, X‐ray diffraction analysis, and scanning electron microscopy. The increase of Al2O3 content at the expense of SiO2 had a marked effect on the mechanism of crystallization and microstructure of glass–ceramics. The glass specimen containing 18 wt% Al2O3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…At the same time, we could see that the area of the exothermic peak of NCAS glass was less than that of NCS, which means the slower crystallization of NCAS glass during the same heat treatment conditions. The difference of the above two glasses could be explained as follows: when Al 2 O 3 is introduced into NCS glass at the expense of SiO 2 , Al 2 O 3 acts mainly as a network former and Al-O-Si bridging bonds could form at the expense of nonbridging oxygen ions of glass [17], resulting in the increase of the viscosity of the glass, T g and T c . In spite of this, the sintering temperatures of both glasses could meet the need of coating design as T c of the glasses was lower than the α to β phase transition temperature of commercial-purity titanium.…”
Section: Resultsmentioning
confidence: 98%
“…At the same time, we could see that the area of the exothermic peak of NCAS glass was less than that of NCS, which means the slower crystallization of NCAS glass during the same heat treatment conditions. The difference of the above two glasses could be explained as follows: when Al 2 O 3 is introduced into NCS glass at the expense of SiO 2 , Al 2 O 3 acts mainly as a network former and Al-O-Si bridging bonds could form at the expense of nonbridging oxygen ions of glass [17], resulting in the increase of the viscosity of the glass, T g and T c . In spite of this, the sintering temperatures of both glasses could meet the need of coating design as T c of the glasses was lower than the α to β phase transition temperature of commercial-purity titanium.…”
Section: Resultsmentioning
confidence: 98%
“…It indicates that the silica content is another reason for the difference of emission intensity. With the decrease of SiO2 content, Al 2 O 3 and Y 2 O 3 are likely to act as network formers in the glasses and a decrease in the content of non‐bridging oxygen ions . The formation of bridging bonds, like Al–O–Si, results in the change of Ce 3+ local environment.…”
Section: Resultsmentioning
confidence: 99%
“…The focus of this paper is on GCs which contain the crystalline phases of diopside and melilite. Several eminent research teams have reported on GCs in the CaO‐MgO‐Al 2 O 3 ‐SiO 2 system in the past decade 37–42 …”
Section: Discussionmentioning
confidence: 99%
“…Table 5 shows that there is, indeed, extremely poor (thorough) documentation on the mechanical properties of potential materials in this quaternary oxide system aiming at dental fixed prosthetic restorations, although this issue is perhaps T A B L E 5 Comparison of the mechanical properties of the glass-ceramics (GCs) produced in the present study with other GCs in the CaO-MgO-Al 2 O 3 -SiO 2 system, reported in literature. [37][38][39][40][41] (the presenting values of fracture toughness were measured by the indentation-Niihara equation)…”
Section: Methods Of Characterizationmentioning
confidence: 99%
See 1 more Smart Citation